How to Prevent, Reduce, and Treat Severe Post Sympathetic Chain Compensatory Hyperhidrosis: 2021 State of the Art - Raveglia, Federico; Orlandi, Riccardo; Guttadauro, Angelo; Cioffi, Ugo; Cardillo, Giuseppe; Cioffi, Gerardo; Scarci, Marco (Frontiers in Surgery, 2022)
The role of thoracic surgery in the management of hyperhidrosis is well known and thoracoscopic sympathetic interruption is commonly accepted as being the most effective treatment. However, some concerns still remain regarding the potential to develop compensatory hyperidrosis (CH), the most troublesome and frequent side effect after surgery and its management. CH prevention may be achieved by identifying subjects at higher risk and/or targeting nerve interruption level on the base of single patient characteristics gathered during the preoperative survey. Furthermore, surgical treatment may consist in different techniques aimed at reversing the effects of previous sympathetic interruption. In regard to predict compensatory hyperhidrosis after sympathectomy, the most interesting proposals in recent literature are a temporary thoracoscopic sympathetic block and the introduction of new and targeted preoperative surveys. If the role of nerve clipping technique versus the definitive cutting is still intensely under debated, new approaches have been recently proposed to reduce the incidence of CH. In particular, extended sympathicotomy has been described as an alternative to overcome severe forms. Lastly, among the techniques developed to reverse sympathetic interruption effect, diffuse sympathicotomy and microsurgical sympathetic trunk reconstruction represent advances in this field. An all-round review of these topics is strongly needed. Our aim is to cover point by point all the above issues. Although sympathectomy represents a small part of thoracic surgery, we believe that it is worthy of interest because of the profound effect that complications for a benign condition can have on patients.